Implementasi Pendidikan Inklusi Pada Mata Pelajaran Pendidikan Agama Islam (Studi Kasus Di Smp Muhammadiyah 2 Malang) - M Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract, the first Education for children with disabilities is Extraordinary School(SLB) as the solution of the children’s condition in order to inprove. In fact, theExtraordinary School (SLB) has some weaknesses, it is because the children withdisabilities, closed to normal, cannot socialize with regular children. So that whenthey graduate the Extraordinary School (SLB), they intend to be rigid and cannotsocialize with people around them. Then, the model of inclusive education comes. Thepurposes of this study were; first, to describe the curriculum model of inclusiveeducation in Islamic Education subject of Junior High School Muhammadiyah 2Malang. Second, how the learning patterns of children with special needs on IslamicEducation subject in Junior High School Muhammadiyah 2 Malang. Third, how thelearning evaluation system of children with special needs on Islamic Educationsubject in Junior High School Muhammadiyah 2 Malang. This study used a qualitativeresearch design through case studies. Data obtained through observations, interviews,and documentations. Data were analyzed by interactive analysis through threeactivities: data reduction, data presentation, and conclusion. Validity of the dataobtained by extension, participation and triangulation data. The results of this studyshowed that, (1) Junior High School Muhammadiyah 2 Malang used two models of thecurriculum, those are modification curriculum and substitution curriculum. (2)Learning patterns of children with special needs on Islamic Education subjects inJunior High School Muhammadiyah 2 Malang used 3 learning patterns. Among themwere learning together pattern without any assistance for those who had highcapability were taught by the subject teachers. Learning together patterns withassistances by a special assistant teacher (GPK) were taught by the subject teachers,and individual learning which was taught directly by a special assistant teacher in theinclusion room. (3) The learning evaluation system of children with special needs onthe subject of Islamic Education in Junior High School Muhammadiyah 2 Malangemphasized two aspects which were the academic and non-academic. Keyword, Islamic Education, Islamic Education in Junior High SchoolMuhammadiyah 2 Malang and the Extraordinary School